Child health care utilisation in families with young or single mothers in a Swedish county. (March 2013) - Wallby, Thomas; Modin, Bitte; Hjern, Anders
Young age and lone parenthood are risk factors for impaired health among mothers and their children. Due to the higher risks of negative influences on physical and mental health, young and single mothers should be of special concern to the Child Health Services (CHS). In the present study, we investigated consumption patterns of child health care services among young and single mothers in Uppsala County, Sweden to study whether they are reached by the universal CHS program and if selective or indicative measures were administered in daily CHS practice. Register data on CHS contacts and socio-demographic indicators were collected for 10692 infants, born in 1998-2006. Results show small differences in contact pattern and immunization status, between children of young versus older, and single versus cohabiting mothers. However, both young (RR 0.64) and single (RR 0.80) mothers had significantly lower rates of participation in parental group. The CHS were consequently successful in implementing the universal preventive child health programme for all families, including families with young or single mothers. There was no indication, however, of an established selective preventive strategy aimed at these high risk families. Programs for strengthening the support provided to vulnerable families by the CHS are needed.